The Influence of the Digital Money System on Waqf Intention with Public Trust As A Mediator - Syafrul Hidayat As; Ida Busnetty (Journal of Creative Power and Ambition (JCPA), 2026)
This study aims to analyze the influence of the use of digital currency systems by waqf institutions on public trust and its impact on waqf intentions. This thinking is based on the premise that public trust in waqf institutions can be strengthened through the application of technology that facilitates transactions and information access, thus strengthening public intentions to make waqf. It is necessary to examine whether digital currency systems significantly influence public trust in waqf programs and impact waqf intentions. This research methodology is quantitative explanatory, with primary data from questionnaires from respondents from various provinces in Indonesia and secondary data from relevant literature studies. The analysis was conducted to evaluate the relationship between the use of digital currency systems and public trust and to identify factors that influence public intentions to make waqf. The results of SEM-PLS testing at the pilot study level with 52 respondents from various cities in Indonesia indicate that digital currency systems, particularly accessibility (ease of use) and system security, influence public trust. The ease and security factors also directly influence waqf intentions. Trust also plays a role in increasing waqf intentions, both as a mediator and as a reinforcement of waqf intentions due to digital system factors. This research can enrich the digital waqf literature, contribute to the development of a sharia-compliant digital currency system, serve as a reference for waqf institutions in implementing a digital currency system, and encourage community participation in waqf. Digital money system, waqf institutions, Islamic finance, public trust, waqf intentions